Differences in gene expression in field populations of Wolbachia-infected Aedes aegypti mosquitoes with varying release histories in northern Australia. - B M C Randika Wimalasiri-Yapa; Bixing Huang; Perran A Ross; Ary A Hoffmann; Scott A Ritchie; Francesca D Frentiu; David Warrilow; Andrew F van den Hurk (Public Library of Science (PLoS), 2023)
Aedes aegypti is the principal mosquito vector of dengue, yellow fever, Zika and chikungunya viruses. The wMel strain of the endosymbiotic bacteria Wolbachia pipientis was introduced into the vector as a novel biocontrol strategy to stop transmission of these viruses. Mosquitoes with Wolbachia have been released in the field in Northern Queensland, Australia since 2011, at various locations and over several years, with populations remaining stably infected. Wolbachia infection is known to alter gene expression in its mosquito host, but whether (and how) this changes over the long-term in the context of field releases remains unknown. We sampled mosquitoes from Wolbachia-infected populations with three different release histories along a time gradient and performed RNA-seq to investigate gene expression changes in the insect host. We observed a significant impact on gene expression in Wolbachia-infected mosquitoes versus uninfected controls. Fewer genes had significantly upregulated expression in mosquitoes from the older releases (512 and 486 from the 2011 and 2013/14 release years, respectively) versus the more recent releases (1154 from the 2017 release year). Nonetheless, a fundamental signature of Wolbachia infection on host gene expression was observed across all releases, comprising upregulation of immunity (e.g. leucine-rich repeats, CLIPs) and metabolism (e.g. lipid metabolism, iron transport) genes. There was limited downregulation of gene expression in mosquitoes from the older releases (84 and 71 genes from the 2011 and 2013/14 release years, respectively), but significantly more in the most recent release (509 from the 2017 release year). Our findings indicate that at > 8 years post-introgression into field populations, Wolbachia continues to profoundly impact expression of host genes, such as those involved in insect immune response and metabolism. If Wolbachia-mediated virus blocking is underpinned by these differential gene expression changes, our results suggest it may remain stable long-term.